Diaphragmatic ultrasound and patent ductus arteriosus in the newborn: A retrospective case series - Dassios, Theodore; Arattu Thodika, Fahad M. S.; Nanjundappa, Mahesh; Williams, Emma; Bell, Aaron J.; Greenough, Anne (Frontiers in Pediatrics, 2023)
Background Patent ductus arteriosus (PDA) and diaphragmatic dysfunction are frequently seen in newborn infants but their relationship remains unknown. We aimed to use point of care ultrasound to compare diaphragmatic kinetics in infants with a PDA compared to in those without a PDA. Methods M-mode ultrasonography was used to measure the mean inspiratory velocity (VI) in newborn infants with and without a haemodynamically significant PDA admitted in the Neonatal Unit at King's College Hospital during a three month period. Results Seventeen diaphragmatic ultrasound studies were reviewed from 14 infants with a median (IQR) gestational age of 26.1 (25.8–30.6) weeks, birth weight of 780 (660–1385) gr at a postnatal age of 18 (14–34) days. Eight scans had evidence of a PDA. The median (IQR) VI was significantly lower in scans with a PDA [1.01 (0.78–1.86) cm/s] compared to the ones without a PDA [3.21 (2.80–3.59) cm/s, p < 0.001]. The median (IQR) gestational age was lower in infants with a PDA [25.8 (25.6–27.3) weeks] compared to infants without a PDA [29.0 (26.1–35.1) weeks, p = 0.007]. Using multivariable linear regression analysis the VI was independently associated with a PDA (adjusted p < 0.001) but not with the gestational age (adjusted p = 0.659). Conclusions Patent ductus arteriosus was associated with a lower mean inspiratory velocity in neonates and this effect was independent of gestational age.